2023
DOI: 10.1097/aln.0000000000004604
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness Research on Spinal versus General Anesthesia for Surgery in Older Adults

Abstract: Comparative effectiveness research aims to understand the benefits and harms of different treatments to assist patients and clinicians in making better decisions. Within anesthesia practice, comparing outcomes of spinal versus general anesthesia in older adults represents an important focus of comparative effectiveness research. The authors review methodologic issues involved in studying this topic and summarize available evidence from randomized studies in patients undergoing hip fracture surgery, elective kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 100 publications
(164 reference statements)
0
1
0
Order By: Relevance
“…The advantages of epidural anesthesia compared to GA have been demonstrated, including better postoperative analgesia, reduced blood loss, better hemodynamic characteristics, reduced stress response, and lower medical costs. 6,25 However, we believe that LA is more convenient and time-saving, and allows for immediate postoperative neurological examination compared to epidural anesthesia. In addition, LA can avoid some specific complications of epidural anesthesia, such as total spinal anesthesia and postoperative urinary retention.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The advantages of epidural anesthesia compared to GA have been demonstrated, including better postoperative analgesia, reduced blood loss, better hemodynamic characteristics, reduced stress response, and lower medical costs. 6,25 However, we believe that LA is more convenient and time-saving, and allows for immediate postoperative neurological examination compared to epidural anesthesia. In addition, LA can avoid some specific complications of epidural anesthesia, such as total spinal anesthesia and postoperative urinary retention.…”
Section: Discussionmentioning
confidence: 96%
“…4 Additionally, the use of GA during these procedures poses a potential risk, especially for elderly patients with comorbidities. [5][6][7] As a result, awake spinal surgery (ASS), a new strategy combining minimally invasive techniques with conscious LA, is increasingly promoted. 8,9 Several studies have demonstrated the benefits of ASS in reducing complications and accelerating postoperative recovery.…”
Section: Introductionmentioning
confidence: 99%